2010
DOI: 10.1007/s00787-010-0130-8
|View full text |Cite
|
Sign up to set email alerts
|

Parental violence and adolescent mental health

Abstract: Being the target of parental violent acts decreases child adjustment and increases the likelihood of mental health problems in childhood and adolescence. Our study analyses how different types of parental violence ranging from verbal threats and swearing to hitting and kicking a child, are associated with child adjustment, indicated by strengths and difficulties scale (SDQ) total problem score, internalizing and externalizing problems as well as prosocial behaviour. We also study whether girls and boys and you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 47 publications
1
53
0
2
Order By: Relevance
“…Structured psychiatric interviews are considered to be the most reliable method to estimate the prevalence of psychiatric diagnoses in a study population, yet the majority of previous studies are based on self-report questionnaires Helweg-Larsen et al, 2011;Peltonen, Ellonen, Larsen, & Helweg-Larsen, 2010) and conducted on general adult Green et al, 2010) or adolescent (McLaughlin et al, 2012) populations.…”
Section: B S T R a C Tmentioning
confidence: 99%
“…Structured psychiatric interviews are considered to be the most reliable method to estimate the prevalence of psychiatric diagnoses in a study population, yet the majority of previous studies are based on self-report questionnaires Helweg-Larsen et al, 2011;Peltonen, Ellonen, Larsen, & Helweg-Larsen, 2010) and conducted on general adult Green et al, 2010) or adolescent (McLaughlin et al, 2012) populations.…”
Section: B S T R a C Tmentioning
confidence: 99%
“…In terms of prevalence, a UK study suggests about 29.5% of children under 18 have been exposed to domestic violence during their lifetime and approximately 5.7% of children and young people, will experience domestic violence in a year (Radford, Corral, Bradley, & Fisher, 2013), and research evidence suggests that its psychosocial impact can be severe. Children who grow up in families affected by domestic violence and abuse have a higher risk of mental health difficulties throughout their lives (Bogat, DeJonghe, Levendosky, Davidson, & von Eye, 2006;Meltzer, Doos, Vostanis, Ford, & Goodman, 2009;Mezey, Bacchus, Bewley, & White, 2005;Peltonen, Ellonen, Larsen, & Helweg-Larsen, 2010), increased risk of physical health difficulties (Bair-Merritt, Blackstone, & Feudtner, 2006); risk of educational drop out and other educational challenges (Byrne & Taylor, 2007;Koenen, Moffitt, Caspi, Taylor, & Purcell, 2003; For some time, researchers and activists have called for recognition of the impact of domestic violence on children in families and the consequent importance of taking children's experiences seriously. For instance, Peled (1996Peled ( , 1998 suggested that children should not be regarded as 'secondary victims' in domestic violence, given the impact of violence on them, while Mullender et al (2003) noted the importance of children's 'active participation' in domestic violence services, suggesting that this meant children "being listened to and taken seriously as participants in the domestic violence situation; and being able to be actively involved in finding solutions and helping make decisions."…”
Section: Introductionmentioning
confidence: 99%
“…Peltonen y col (8), en un estudio realizado en una muestra simple comunitaria en adolescentes de 15 a 16 años de Finlandia (n= 5,762) y Dinamarca (n= 3,943) encontró que la violencia parental se relacionaba con síntomas internalizantes (síntomas de ansiedad o depresión) y externalizantes en adolescentes (agitación y pobre conducta prosocial).…”
Section: Vargas Murga Hunclassified
“…Por otro lado, en el caso de los adolescentes, se ha estudiado más el efecto de la exposición a la violencia contra la mujer, que el efecto de esta violencia independiente de la exposición (6)(7)(8), encontrándose relación con problemas de salud mental diversos.…”
Section: Introductionunclassified